Assessing Biodiversity Conservation of the Cricetidae Family in Afghanistan’s Mountain Ecosystems - Jafari , Mohammad Hassan; Teimoory, Narges; Qurbani, Nazifullah (Journal of Natural Sciences – Kabul University, 2026)
This study provides the first Afghanistan-led assessment of small mammal biodiversity within Afghanistan’s critical mountain ecosystems, focusing on three Cricetidae species (Microtus transcaspicus, Cricetulus migratorius, and Ellobius fuscocapillus) identified across Bamyan and Kabul provinces. Specimens were analyzed using morphological, morphometric, and chromosomal methods. The findings reveal distinct taxonomic classifications among the three genera, underscoring the hidden diversity of Afghanistan’s Cricetidae family. This work addresses a critical knowledge gap in a region where biodiversity loss is exacerbated by habitat fragmentation and limited conservation research. Species such as Ellobius fuscocapillus, a burrowing rodent, play essential ecological roles in soil nutrient cycling and plant community dynamics, highlighting their importance for maintaining ecosystem integrity. We emphasize the urgent need for habitat protection and community engagement to safeguard small mammals, which serve as vital bio indicators of ecosystem health in rapidly degrading mountain landscapes.